Mengembangkan Kecerdasan Anak melalui Pendidikan Usia Dini - Rakhmawati, Istina (PIAUD Universitas Islam Negeri Sunan Kudus, 2015)
Nowadays there are many parents who recruit children to haveeducation until junior high school or vocational school. It is because of financialcase and parents just follow the attitude of society in general. Going to school isnot a requirement but merely the fulfillment of social needs. They are afraid tosay miser for not sending their children, their worries will be removed from thesocial community for not sending their children, and there are also those who feelguilty if they do not send their children there. In short, the school is only as thefulfillment of social needs. What happened to these people? Apparently, they neversend children and grandchildren since hereditary. If they go to school, it is just asa formality, so that education will have no impact on the change in mindset andbehavior in everyday life. Their children already can be sure to have “poisoned”with the mindset that is not profitable, so they receive only for the school and thisagainst the current by the word of God, which means: “O ye who believe, guardyourselves and your families from a fire hell that fuel is men and stones; guardianangels of the rough, tough, who do not disobey Allah in what He commands themand always do what they’re told.”